The epidemiology of injuries in South African high school soccer players - Ramathesele, Jonas Ramorwesi (MRC/UCT RU for Exercise and Sport Medicine, 2017)
The aim of the study was to document the epidemiology of injuries sustained by South African high school soccer players. Subjects for the study were selected from all the high schools (n = 10) in Tembisa (Gauteng, South Africa). A cohort of 227 high school soccer players, representing all the players in the Tembisa schools, was followed over one playing season. All practice and match hours were recorded and specific injury report forms were completed by all the coaches. All injured players were then referred to the principal investigator (JR) for detailed examination to document injuries. Factors such as pre-season training, warm-up, stretching, playing surface, environmental factors, and the use of protective equipment were also recorded. In this study, 63% of all the players sustained an injury during the season (seasonal incidence). The overall incidence of injuries was 9.04/1000 hours of play. The incidence in matches was 274 times higher than in practice. More than half (57%) of the injuries were classified as moderate. The highest incidence of injury per player position was in goalkeepers (13.7/1000 hours play). The lower extremity accounted for most injuries (88.8%), principally the ankle (42.4%) and the knee (27.1%). The most common type of injury was a ligamentous sprain (68%), followed by musculotendinous strains (15.8%). There were only two joint dislocations, and no fractures. All the participants in this study played on gravel pitches and on no occasion was a first-aid kit available. The majority of players were not aware of appropriate stretching, warm-up, and strapping techniques to prevent injuries. None of the players engaged in any form of pre-season training. In two of the schools (20%) the soccer coaches had formal training with coaching certification. Although the injury rate in high school soccer players in this study is only slightly higher than that reported · by others, it is clear that scientifically based measures of injury prevention (pre-season training, warm-up, stretching, and strapping) need to be implemented in these schools. In addition, proper sports and first-aid facilities should be provided, and coaches should receive formal continuous training.